The Role of Constitutional Law In Character-Forming Education In Higher Education - Handoko, Panggung (International Journal of Educational Research & Social Sciences, 2025)
Character education in higher education plays a strategic role in shaping a generation of the nation with integrity, democracy, and adherence to constitutional principles. In this context, Constitutional Law serves as a normative framework governing the implementation of national education, including the mandate to shape student character. This study aims to analyze how the principles of Constitutional Law—such as constitutional supremacy, good governance, and human rights protection—play a role in formulating and directing character education policies in higher education. This study uses a juridical-normative approach by examining the legal norms contained in the 1945 Constitution of the Republic of Indonesia, Article 31 paragraph (3) concerning the objectives of national education, Law No. 12 of 2012 concerning Higher Education, and Law No. 20 of 2003 concerning the National Education System. The results of the study indicate that State Administrative Law provides a strong constitutional foundation for the development of character education through the affirmation of moral values, public ethics, and citizen responsibility. In addition, higher education regulations mandate the integration of character in the curriculum, university governance, and the formation of a civilized academic culture. This study concludes that the role of Constitutional Law is not limited to normative aspects, but also encompasses oversight, institutional strengthening, and the guarantee of systematic character education implementation. Effective implementation requires regulatory harmonization, commitment from higher education institutions, and synergy between the state and society in shaping students' character as citizens based on the values ​​of Pancasila and the constitution.